Relevance of Angiotensin Converting Enzyme Gene Polymorphism rs2285666 with Hypertension in Type 2 Diabetes Mellitus - Hummady, Shaimaa Addai; Algenabi, Abdul Hussein (Medical Science Journal for Advance Research, 2024)
Background: Cardiovascular disease is common in diabetes, and is connected with activation of the renin-angiotensin system (RAS). Angiotensin-converting enzyme (ACE)2 is a recently described member of the RAS, and this study investigated ACE2 polymorphisms associated with hypertension and T2DM. It was linked to increased chances hypertension was a significant peripheral vascular issue, including both macro- and microvascular complications. Aim of the study: To evaluate the risk of ACE2 gene polymorphisms (rs2285666) in the development of hypertension and also to estimate the ACE2 levels in the recruited individuals and relevance with the analyzed SNP Method: Variant ACE2 (rs2285666) examined in 200 Iraqi subject’s diabetics with and without hypertension. 90 HT diabetic patients (case group) and 110 NT diabetic patients (control group) were included. Patients aged>30 years old and patients diagnosed by physicians as having T2DM with and without hypertension. Exclusion criteria include patients who have T1DM or need insulin injections. assessments were determined for each patient: age, sex, body mass index (BMI), diabetes, blood pressure, (FBS), (HbA1c), (Chol), (LDL), (HDL), (TG) andACE2serum conc. Polymerase chain reaction (PCR) is used to detect the G/A alleles. (Chi-squared and t-test) (odds ratios) were applied to determine the association between G/A polymorphism and hypertension. P<0.05 was considered statistically significant. Results: Results of analysis of the rs2285666 G>A pointed out a significant association with the development of hypertension. After adjusting for age, sex, and BMI in the co-dominant model, heterozygous (GA) significantly distended the danger of hypertension by three folds with deference to those of the wild homozygous (GG) (OR = 3.11, CI 95% = 1.04-9.34, P = 0.042). In the same way, the homozygous (AA) genotype suggestively raised the risk of hypertension by onefold (OR= 1.49, CI 95%; 0.82-3.21, P= 0.039). Conversely, both dominant and recessive inheritance patterns were associated with an increased risk in diabetic patients with HT. The dominant model showed an odds ratio (OR) of 1.56 (95% confidence interval CI: 1.72-4.21, P = 0.001), while the recessive model showed an OR of 2.13 (95% CI: 1.74-6.21, P = 0.021). The minor allele (A) frequency in HT patients (0.17) was found to be significantly (P=0.022) decreased when linked to the NT diabetic control groups. Conclusion: ACE2 gene polymorphism, mutant homozygous (AA) and heterozygous (GA) genotypes, rs2285666, are associated with hypertension in T2DM Iraqi population with a 2 folds risk factor to develop the disease as well as differences in serum lipid concentrations are not influenced by the ACE2 gene polymorphism rs2285666 genotypes.